Prostatic artery embolization in patients with benign prostatic hyperplasia: perfusion cone-beam CT to evaluate planning and treatment response. - Pandolfi, Marco; Liguori, Alessandro; Gurgitano, Martina; Arrichiello, Antonio; Di Meglio, Letizia; Rodà, Giovanni Maria; Guadagni, Alice; Angileri, Salvatore Alessio; Ierardi, Anna Maria; Buccimazza, Giorgio; Donat, Daniela; Paolucci, Aldo; et al. (Acta Biomedica Atenei Parmensis, 2020)
This proof of concept is to evaluate the utility of perfusion cone-beam computed tomography (CT) in patients undergoing prostatic artery (PA) embolization (PAE) for benign prostatic hyperplasia (BPH) with moderate or severe-grade lower urinary tract symptoms (LUTS). PAE is a novel minimally invasive therapy and is both safe and effective procedure with low risks and high technical successes, making this procedure as the best alternative to surgery. A lot of technical changes would compromise clinical outcomes after procedure, including a variable prostate vascular anatomy, thin PA, and extensive atherosclerotic disease. The purpose of our study is to exploit the advantages of Perfusion Cone Beam Computed Tomography (CBCT) that could impact treatment and help interventional radiologists for treatment planning, diagnosis and for assessing the technical feasibility during PAE, mitigating the risk of nontarget embolization and suggesting clinical outcomes. Qualitative and quantitative clinical pre- and post-treatment values will be compared, to reach the best possible results.